Components and Characteristics of a Psychiatric Partial Hospital Military Program. - Lande, R. Gregory; Pourzand, Miriam (Military Medicine, 2016)
This article describes the components of a psychiatric partial hospital military program and the characteristics of referrals received over the 5-year period from 2009 to 2013. The 5-year study period included ongoing combat operations in Iraq and Afghanistan along with their subsequent troop withdrawals and change in mission. A total of 1,194 service members were referred for this level of care, and even with the changing battlefield conditions, the number of psychiatric referrals remained steady throughout the 5-year period, with a significant spike in admissions in 2013. The principal diagnoses were major depressive disorder and post-traumatic stress disorder. One-third of the admissions came from service members with 4 to 8 years' time in service and slightly more than one-third were employed in direct combat roles or medical support. In terms of gender, females accounted for one-quarter of the admissions.